Manifestaciones clínicas Covid-19 - Bretón I, Andrea; Tordecilla F, Rocío (Revista Hospital Clínico Universidad de Chile, 2021)
The current SARS-CoV-2 pandemic originated in China in late 2019, when an outbreak of pneumonia cases of unknown cause raised suspicions of an emerging infectious agent. More than 1 year after the identification of this new coronavirus, it has already caused more than 100 million cases worldwide. Coronavirus Disease 2019 (Covid-19), as defined by the WHO in February 2020, has a diverse clinical presentation from asymptomatic individuals to multi-organ failure and death. In this review, we will describe the main clinical manifestations of Covid-19 in adults.